SAT0166 Serum cytokine and chemokine profiling in primary sjögren's syndrome. (23rd January 2014) - Tarn, J.; Mitchell, S.; Bowman, S.; Price, E.; Pease, C.; Sutcliffe, N.; Emery, P.; Andrews, J.; Bombardieri, M.; Pitzalis, C.; Lanyon, P.; Hunter, J.; et al.
Abstract : Background: Primary Sjögren's syndrome (pSS) is a multisystem autoimmune disease characterised by salivary and lacrimal gland inflammation leading to glandular destruction. The pathogenesis of pSS remains unclear, and research into pSS is made more challenging due to the heterogeneous clinical phenotypes among pSS patients. Several serum cytokines and chemokines have been linked with pSS pathogenesis, but their role in the various clinical manifestations in pSS have not been fully explored 1, 2 . Objectives: In this study, we examine the serum samples of a large cohort of clinically well-characterised PSS patients 3 in order to determine whether serum cytokines and chemokines may be used to differentiate PSS patients from healthy controls, and if so, the relationship between these serum abnormalities and clinical phenotypes. Methods: Serum levels of 24 different cytokines, chemokines and adhesion molecules for 150 pSS patients and 30 healthy controls were measured using Cytometric Bead Array.PSS patients were further classified into the following subsets: 1) Lymphoma; 2) No Lymphoma; 3) High systemic disease activity (ESSDAI score >12); 4) Low systemic disease activity (ESSDAI <1); 5) High residual glandular function (Oral salivary flow (OSF) >10ml/15min and Schirmer's test >10cm); 6) Low residual glandular function (OSF <1ml/15min and Schirmer's test <1cm); 7) Anti-Ro and Anti-La positive; 8) Anti-Ro and Anti-La negative. The relationship between analyte levels and clinical and laboratory parameters of PSS was examined using multivariate analysis and Mann-Whitney U testing; p-values were Bonferroni corrected for multiple comparisons. Results: There were marked differences in the levels of many cytokines and chemokines between PSS patients and healthy controls, with a p value <0.001, statistically significant after Bonforroni's correction for multiple comparisons. Serum IL4 and IL17 were found to be significantly higher in patients versus controls. Chemokines such as MIG (CXCL9), MIP1a (CCL3) and MIP1b (CCL4), IP10 (CXCL10), were also measured at higher levels in patient serum. Serum levels of IFNa, LTα and TNFα also differ significantly between patients and controls. Differences in cytokine levels were observed between patient subsets which were no longer significant after Bonferroni correction. Conclusions: Differences in blood cytokine and chemokine levels between primary Sjogren's patients and controls can be detected in serum. Serum MIG (CXCL9), MIP1a (CCL3) and MIP1b (CCL4), IP10 (CXCL10) IFNa, LTA and TNFa levels differ significantly between patients and controls. Our observations raise the possibility that these analytes may be important in disease pathogenesis. References: Baturone, R. et al. Scand. J. Immunol. 2009;38:386. Szodoray, P. et al. Scand. J. Immunol. 2004;59:592. Ng, W.F. et al. Rheumatology 2010;50:32. Disclosure of Interest: None Declared